Pengaruh Pendidikan Kesehatan dengan Media Audiovisual tentang Pencegahan Keputihan terhadap Pengetahuan dan Sikap Remaja Putri - Sufiati, Sufiati; Andayani, Sri Astutik; Munir, Zainal (Universitas Nurul Jadid, 2025)
Vaginal discharge is one of the most common reproductive health problems experienced by adolescent girls, often causing discomfort, reducing self-confidence, and potentially leading to more serious reproductive health issues if not properly managed. Limited knowledge and negative attitudes toward genital hygiene are among the contributing factors to its high prevalence. Health education using audiovisual media is considered an effective strategy for delivering health messages, as it combines visual and auditory elements that are more engaging, easier to understand, and capable of improving information retention. This study aims to analyze the effect of audiovisual-based health education on adolescent girls’ knowledge and attitudes regarding the prevention of vaginal discharge. A quasi-experimental design with a pretest-posttest control group was applied, involving 60 students equally divided into intervention and control groups selected through total sampling. The research instrument consisted of validated and reliable questionnaires measuring knowledge and attitudes. Data analysis was conducted using the Wilcoxon test, revealing a significant improvement in the intervention group after receiving audiovisual health education (p < 0.05), while no meaningful change occurred in the control group. These findings indicate that audiovisual health education is effective in enhancing adolescents’ understanding and fostering positive attitudes toward the prevention of vaginal discharge. Consequently, the approach is recommended for integration into school health programs and community-based interventions as an innovative and sustainable method to promote reproductive health among adolescents.